Recognition, Coexistence, and Civic Trust in Gerbang Mas Perkasa Transmigration Area, Sambas Regency, West Kalimantan - Fristian Hadinata (Utan Kayu Publishing, 2026)
This article examines how coexistence in the Gerbang Mas Perkasa transmigration area, Sambas Regency, West Kalimantan, can be understood through Charles Taylor's politics of recognition. The area is a border transmigration zone in which transmigrant and local communities live within a plural society marked by historical memory, economic vulnerability, ecological pressure, and uneven public services. Drawing on field data from the 2025 Patriot Expedition report, this study uses a descriptive qualitative design supported by survey data from 243 respondents, interviews, focus group discussions, observation, and secondary documents. The findings show that everyday coexistence is not merely the absence of conflict. It is sustained by practical cooperation, shared economic spaces, local-national attachment, and institutional mediation. However, formal tolerance remains insufficient when public trust is weakened by infrastructure gaps, unequal access to economic opportunities, and unresolved perceptions of distributive justice. Using Taylor's recognition framework, the article argues that sustainable transmigration governance requires more than administrative integration. It requires recognition-based governance that protects cultural identity, strengthens intergroup relations, and converts coexistence into civic friendship and solidarity. The article contributes to debates on transmigration, border development, and multicultural governance by proposing a modest analytical model linking recognition, public trust, and plural-society resilience in Indonesian border communities